Tourism, leisure and land management and development - Brown, Stephen; Harrison, David, 1941- (Real estate management., 2004)
Simultaneously hailed as the saviour of developing countries and reviled as one of the great despoilers of our environment, travel and tourism is now an industry of global scale, and 2002 saw the number of international tourists exceed 700 million for the first time - the equivalent to over one in ten of the entire population of the world travelling on holiday. The papers that have been brought together in this special issue on tourism reflect the fact that tourism is about more than just people travelling to exotic locations. It is a business, like any other, with the same need to consider seriously and carefully the real estate requirements of the business. And, like many other businesses, there is a diverse range of stakeholders.